Magnetized Quark and Strange Quark Matter in the Higher Dimensional Spherically Symmetric Space Time Admitting One Parameter Group of Conformal Motions. Issue 1 (2nd January 2022) - Kumbhare, Saroj R.; Khadekar, G.S.
Abstract: In present paper, we have studied magnetized quark and strange quark matter with conformal motions in higher dimensional spherically symmetric space-time. We found Einstein's eld equations in higher dimensional spherically symmetric space-time using conformal motions. In the framework of higher dimension, various physical quantities have discussed.